Managing the symptoms of Huntington's disease. Issue 2 (25th February 2020) - Patrick, Craig; Ritchie, Stuart
Abstract : Unfortunately, there is currently no cure for Huntington's disease and management is therefore focused on alleviating symptoms. This article discusses the treatment options available for managing the motor and psychiatric symptoms associated with Huntington's disease.